2023
DOI: 10.3390/su15118975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Treatment on the Physical and Chemical Properties of Ice Cream with a Strawberry Seed Oil Oleogel

Sybilla Nazarewicz,
Katarzyna Kozłowicz,
Bożena Gładyszewska
et al.

Abstract: This study presents the impact of an ultrasonic treatment (UT) as an alternative to traditional, standard pasteurization (PT) on selected properties of ice cream. Additionally, an oleogel from strawberry seed oil was included in the ice cream recipe as a fat component in the shares of 5%, 6%, and 7%. To evaluate the ultrasound’s effect on the ice cream’s properties, an analysis of the ice cream’s chemical composition was conducted, including the total content of polyphenols and macro- and microelements, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“… Category Oleogel Product type Conditions Results References Cheese high-oleic soybean oil (HOSO) and rice bran wax oleogel-cream-cheese (OCC) OG sample was added to skim milk (76.58 %) The fatty-acid profiles, antioxidant content, and the amount of oxidation products were comparable between the OCC and the ungelled cream-cheese sample (UGCC) products. ( Park et al, 2018 ) Canola oil with carnauba wax imitation cheese low in saturated fat The addition of oleogel is about 10 % Oleogel produced cheese with harder and more cohesive/chewy textures ( Moon et al, 2021 ) Soybean oil with rice bran wax (RBW) or sunflower wax(SW) Processed cheese products (PCP) Contains 10 % oleogel The texture of PCP with 10 % oleogel(RBW) is harder, and the meltability is increase ( Huang et al, 2018 ) Ice cream refined sunflower oil with beeswax Ice cream 90 g raw cream (50 % milk fat) or oleogel Reduced the amount of saturated and long-chain fatty acids; organoleptic qualities deteriorated ( Ozdemir, 2023 ) soybean oil, with 6 % carnauba wax Ice cream 50 %∼100 % replacement of the traditional lipid The replacement of oleogel fat (50 %) reduced the melting rate of ice cream, and sensory evaluations is acceptable ( Airoldi et al, 2022 ) Camellia oil with and beeswax Ice cream The amount of oleogel addition was 7 % Compare with camellia oil ice cream and butter ice cream, the oleogel ice cream is better at overrun rate, melting rate and nutrition ingredients ( Jing et al, 2022 ) Strawberry seed oil with hydroxypropyl methylcellulose Ice cream Replace 5–7 % fat content Rich in unsaturated fatty acids, a promising alternative ( Nazarewicz et al, 2023 ) Cream Isolated soy protein (ISP) and basil seed gum (ISP-BSG) Cream cream produced with reduced fat (5, 10 and 15 %) 5 % replacement had the most value of overall acceptance at texture and sensory test ( …”
Section: Types and Characteristics Of Oleogel In Dairy Productsmentioning
confidence: 99%
“… Category Oleogel Product type Conditions Results References Cheese high-oleic soybean oil (HOSO) and rice bran wax oleogel-cream-cheese (OCC) OG sample was added to skim milk (76.58 %) The fatty-acid profiles, antioxidant content, and the amount of oxidation products were comparable between the OCC and the ungelled cream-cheese sample (UGCC) products. ( Park et al, 2018 ) Canola oil with carnauba wax imitation cheese low in saturated fat The addition of oleogel is about 10 % Oleogel produced cheese with harder and more cohesive/chewy textures ( Moon et al, 2021 ) Soybean oil with rice bran wax (RBW) or sunflower wax(SW) Processed cheese products (PCP) Contains 10 % oleogel The texture of PCP with 10 % oleogel(RBW) is harder, and the meltability is increase ( Huang et al, 2018 ) Ice cream refined sunflower oil with beeswax Ice cream 90 g raw cream (50 % milk fat) or oleogel Reduced the amount of saturated and long-chain fatty acids; organoleptic qualities deteriorated ( Ozdemir, 2023 ) soybean oil, with 6 % carnauba wax Ice cream 50 %∼100 % replacement of the traditional lipid The replacement of oleogel fat (50 %) reduced the melting rate of ice cream, and sensory evaluations is acceptable ( Airoldi et al, 2022 ) Camellia oil with and beeswax Ice cream The amount of oleogel addition was 7 % Compare with camellia oil ice cream and butter ice cream, the oleogel ice cream is better at overrun rate, melting rate and nutrition ingredients ( Jing et al, 2022 ) Strawberry seed oil with hydroxypropyl methylcellulose Ice cream Replace 5–7 % fat content Rich in unsaturated fatty acids, a promising alternative ( Nazarewicz et al, 2023 ) Cream Isolated soy protein (ISP) and basil seed gum (ISP-BSG) Cream cream produced with reduced fat (5, 10 and 15 %) 5 % replacement had the most value of overall acceptance at texture and sensory test ( …”
Section: Types and Characteristics Of Oleogel In Dairy Productsmentioning
confidence: 99%
“…Melting properties of ice cream samples were determined by methods described by Liu et al (2022) and Nazarewicz et al (2023), with slight modifications. The starting mass of each sample was measured.…”
Section: Melting Properties Determinationmentioning
confidence: 99%
“…Güven et al [ 42 ] observed that the pH value of olive oil ice cream samples increased, and olive oil worsened ice cream melting. The properties of ice cream with oleogels from various seed oils (strawberry seed oil; tomato seed oil) were investigated by Nazarewicz et al [ 43 ] and Nazarewicz et al [ 44 ]. They observed that various characteristics of ice creams were affected with the increase in oleogel proportions.…”
Section: Introductionmentioning
confidence: 99%